Utilization of Crude Oil as an Alternative Oil Base Mud Drilling Operation by â€œVICOILâ€ Standard Drilling Simulation Rig in MGTM Well UPN â€œVeteranâ€ Yogyakarta Education Park Mineral Geotechnology Museum Field - KRT Nur Suhascaryo; Endah Wahyurini; Yuan Cahyo Guntoro (Scientific Contributions Oil and Gas, 2021)
Shale is one of the rocks that often causes drilling problems because shale tends to swell or swell when in contact with mud filtrate, mainly Water-base Mud (WBM). This study aims to determine how the performance of Oil-base Mud (OBM) based on Crude Coconut Oil (CCO) in overcoming the swelling problem. The methodology used consists of drilling simulation and cutting analysis in the X-Ray Diffraction (XRD) laboratory. The series of activities in the study began with the preparation of rock layers, followed by testing the penetration rate using Water-base Mud as a comparison. After cutting analysis was carried out in the XRD laboratory of UPN â€œVeteranâ€ Yogyakarta with the Rigaku tool, then replaced the type of drilling fluid Oil-base Mud with basic materials alternative to Crude Coconut Oil (CCO) and followed by a penetration test. Rate of Penetration (ROP) test results from WBM with Rheology 1 at interval A or a depth of 1.96 ft-4.92 ft is 442.8 ft/h, Rheology 2 at interval B or a depth of 4.92-10.5 ft is 118.5 ft/hr on the first day. Swelling occurred and results in pipe sticking at depth of 6.5 ft. Based on the Bulk Mineral analysis, clay mineral content is 23.84%. Based on the Clay Oriented, smectite dominates the clay by 29.09%. Based on MBT, shale belongs to class B (illite and mixed-layer montmorillonite illite), where this mineral can expand. Based on a Geonor As test, 5.18% of the cutting can develop when exposed to water. The drilling fluid was replaced with Oil-base Mud based on alternative Crude Coconut Oil (CCO), and obtained ROP Rheology 1 at Interval A of 492 ft/h and Rheology 2 at Interval B of 480 ft/h. The results of the Compressive Strength test interval A on the first, third, and fifth days were 31,699 psi, 42,265 psi, and 52,831 psi. The results of the Compressive Strength test interval B on the first, second, and third days were 31,496 psi, 41,517 psi, and 52,971 psi. Based on clay mineral analysis and magnitude of ROP value, is known that Crude Coconut Oil (CCO) based Oil-base Mud is effective because during the simulation, there are no drilling problems, and the resulting ROP value is greater than the first day Water-base Mud.